(untitled) (Global Scientific Review, 2024)
This article discusses the Sitorai Mohi Khosa palace garden, built in the late 19th and early 20th centuries in Bukhara. The article explores the architectural and compositional solutions of the palace, its traditional artistic decorations, and the integration of both modern and national architectural styles and elements. The creative works of the architects and craftsmen involved in its construction are also examined